Summe seiner Teile?: Überlegungen zum doppelten Skarabäus mit Menschenkopf Berlin ÄM 11405 - Backes, Burkhard (Zeitschrift für ägyptische Sprache und Altertumskunde, 2019)
New interpretation of Berlin, Ägyptisches Museum 11405. The object shows traces of voluntary mutilation not dissimilar to the much older ‘reserve heads’. Some elements have been left unfinished. In the light of iconographic parallels in some reliefs, the combination of two embracing scarabs with a human head is identified as an image of Ptah as creator-god.